Systematic Monitoring of Cognition for Adults With Cerebral Palsy—The Rationale Behind the Development of the CPCog-Adult Follow-Up Protocol - Stadskleiv, Kristine; van Walsem, Marleen R.; Andersen, Guro L.; Bergqvist, Lena; Bøttcher, Louise; Christensen, Klaus; Heyerdahl, David; Hollung, Sandra Julsen; Høye, Helene; Jahnsen, Reidun; Klevberg, Gunvor L.; Lindquist, Barbro; et al. (Frontiers in Neurology, 2021)
Cerebral palsy (CP) comprises a heterogeneous group of conditions recognized by disturbances of movement and posture, and is caused by a non-progressive injury to the developing brain. Birth prevalence of CP is about 2–2.5 per 1,000 live births. Although the motor impairment is the hallmark of the diagnosis, individuals with CP often have other impairments, including cognitive. Cognitive impairments may affect communication, education, vocational opportunities, participation and mental health. For many years, CP has been considered a “childhood disability,” but the challenges continue through the life course, and health issues may worsen and new challenges may arise with age. This is particularly true for cognitive impairments, which may become more pronounced as the demands of life increase. For individuals with CP, there is no one-to-one correlation between cognition and functioning in other areas, and therefore, cognition must be individually assessed to determine what targeted interventions might be beneficial. To facilitate this for children with CP, a systematic follow-up protocol of cognition, the CPCog, has been implemented in Norway and Sweden. However, no such protocol currently exists for adults with CP. Such discontinuity in health care services that results from lack of follow-up of cognitive functioning and subsequent needs for adjustments and interventions, makes transition from pediatric to adult health care services challenging. As a result, a protocol for the surveillance of cognition in adults with CP, the CPCog-Adult, has been developed. It includes assessment of verbal skills, non-verbal reasoning, visual-spatial perception, and executive functioning. It is recommended to perform these assessments at least once in young adulthood and once in the mid-fifties. This report describes the process of developing the CPCog-Adult, which has a threefold purpose: 1) to provide equal access to health care services to enable the detection of cognitive impairments, 2) to provide interventions that increase educational and vocational participation, enhance quality of life, and prevent secondary impairments, and 3) to collect systematic data for research purposes. The consent-based registration of data in the well-established Swedish and Norwegian national CP registries will secure longitudinal data from childhood into adulthood.